Comparative sequence analysis of the capsular polysaccharide loci of Actinobacillus pleuropneumoniae serovars 1–18, and development of two multiplex PCRs for comprehensive capsule typing - Bossé, Janine T. (Vet Microbiol, 2018)
Problems with serological cross-reactivity have led to development of a number of PCRs (individual and multiplex) for molecular typing of Actinobacillus pleuropneumoniae, the causative agent of porcine pleuropneumonia. Most of these assays were developed for detection of specific amplicons within capsule biosynthetic genes before the availability of complete sequences for the different serovars. Here we describe comparative analysis of the complete capsular loci for all 18 serovars of A. pleuropneumoniae, and development of two multiplex PCRs for comprehensive capsule typing of this important pig pathogen.